Physicochemical properties of alpha-mangostin loaded nanomeulsions prepared by ultrasonication technique - Rathapon Asasutjarit; Tunradee Meesomboon; Pheeraphong Adulheem; Siriporn Kittiwisut; Papawee Sookdee; Worada Samosornsuk; Asira Fuongfuchat (Heliyon, 2019)
Hypothesis: Alpha-mangostin (AMG) is a natural compound possessing strong antibacterial activity. Because of its poor water solubility, the formulations of AMG usually require high concentrations of solubilizers leading limitation for using in some clinical applications. Thus, the novel formulation of topical nanoemulsion (NE) containing AMG (AMG-NE) with optimal content of the oil phase and surfactants was developed. Experiments: AMG was extracted, purified and used as an active ingredient of AMG-NE. Blank NEs (NEs without AMG) with varying in contents of the oil phase and surfactants and AMG-NE were prepared by the ultrasonication technique. They were investigated their physicochemical properties including antibacterial activity against Staphyloccocus aureus and Propionibacterium acnes (which is recently renamed as Cutibacterium acnes). Findings: Blank NEs and AMG-NE had droplet size in a range of nanometer and negative value of zeta potential. The droplet size, polydispersity index and zeta potential of blank NEs were affected by formulation compositions and sonication intensities. AMG could be loaded into a representative Blank NE at a maximum concentration of 0.2% w/w and did not cause significant changes in physicochemical properties. AMG-NE showed the antibacterial activity against Staphyloccocus aureus and Propionibacterium acnes without toxicity to the skin cells. Therefore, AMG-NE had potential for using in a clinical study to investigate its efficacy and safety in patients.